Does the Role of Corporate Governance can Improve Financial Performance? Bibliometric Literature Review - Novtiani, Rozida; Juliarto, Agung (Journal of Applied Accounting and Taxation, 2025)
The objective of this study is to examine research trends on the role of corporate governance in financial performance across various countries, published in the Scopus database from 2019 to 2024. Data collection was conducted on May 24, 2024. The research method used was qualitative with bibliometric analysis using the R-Packages software and the Biblioshiny Web Interface for processing and visualizing data. For conciseness and professionalism, the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines were used. The PRISMA method and bibliometric analysis are combined to strengthen the quality and scope of the literature review. PRISMA is used in the initial stage to systematically screen the literature. The bibliometric analysis is based on preset inclusion and exclusion criteria, applied at the end of the screening process to analyze and visualize data from the selected publications.  There are five stages in this research: using keywords relevant to the research topic, searching for data matching the keywords, selecting articles, validating the data, and analyzing the data. One of the most influential publications is Tan Y's research, which has been cited 194 times since its 2022 publication. The affiliate with the most publications is the University of Delhi, with 15, while China is the most productive country, with the highest number of citations at 154.